Findings from the Global Burden of Disease Study 2021 - Murray, Christopher J L (The Lancet (British edition), 2024)
In The Lancet, we have published the findings of the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021 in a series of six Articles.1–6 GBD began in 1991 and has continued over the past three decades to provide a comprehensive empirical assessment of health around the world.7 With each iteration GBD has become more detailed, including more causes, risks, and locations, improving granularity of age group analyses, and has enabled the completion of extension studies, such as forecasting studies and estimations of the burden of antimicrobial resistance.8–14 This greater detail has been possible because of the large increase in primary data sources, with 328 938 different sources used in GBD 2021, enabling the calculation of more than 607 billion estimates. [...]because of inadequate data systems and huge lags in alternative measurement methods for age-specific and cause-specific mortality, controversy remains about the true impact of COVID-19 in sub-Saharan Africa. [...]the Civil Registration and Vital Statistics system in South Africa showed large increases in mortality rates in older age groups during the pandemic;1,3 however, Health and Demographic Surveillance Sites in the country have largely not reported on the effects of the COVID-19 pandemic even as of January, 2024.3 Preliminary all-cause mortality reporting from countries such as Canada, Finland, Japan, and Australia suggests much larger than expected increases in mortality in 2022 and 2023. By contrast, slow decreases or the beginning of decreases in estimated total fertility rates in western sub-Saharan Africa—from 6·94 (95% UI 6·62–7·25) in 1950, to 4·29 (4·03–4·58) in 2021, and 2·72 (2·32–3·15) in 2050—mean that the total population for the whole of sub-Saharan Africa will probably continue to grow, potentially until the end of the century.2 Climate stress, increasing educational attainment, and efforts to give women access to reproductive health services might accelerate the decline in fertility.